Dread Objects - Brian, Kathleen (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2026)
This is an account of dread objects — madness, suicide, suicidality — as they moved through the normalized and normalizing terrain of an emergent nineteenth-century US security state. Tracking them in this way, while also attending to the affective and temporal registers in which they were articulated, reveals a consequential distinction between intervention and prevention. The latter, still nascent at mid-century, cooperated with actuarial ways of thinking that continue to inform normative standards for engaging the past. This account doubles as lament. Addressing itself to the fundamental violence at the root of such standards, while also attending to what has been lost by way of them, it asks what methods and forms are made possible by disability as analytic and as epistemology.